Xin-Ji-Er-Kang Alleviates Isoproterenol-Induced Myocardial Hypertrophy in Mice through the Nrf2/HO-1 Signaling Pathway. (22nd August 2022) - Yu, Ting-Ting; Sun, Li-Jun; Chen, Chen; Wang, Zi-Jian; Liu, Xue-Sheng; Zhu, Feng-Qin; Gao, Shan
Abstract : Xin-Ji-Er-Kang (XJEK) inhibited cardiovascular remodeling in hypertensive mice in our previous studies. We hypothesized that XJEK may prevent isoproterenol (ISO)-induced myocardial hypertrophy (MH) in mice by ameliorating oxidative stress (OS) through a mechanism that may be related to the nuclear factor erythroid 2-related factor 2 (Nrf2)/heme oxygenase-1(HO-1) pathways. Forty SPF male Kunming mice were randomized into 5 groups ( n = 8 mice per group): control group, MH group, MH + different doses of XJEK (7.5 g/kg/day and 10 g/kg/day), and MH + metoprolol (60 mg/kg/day). On the eighth day after drug treatment, electrocardiogram (ECG) and echocardiography were performed, the mice were sacrificed, and blood and heart tissues were collected for further analysis. XJEK administration markedly ameliorated cardiovascular remodeling (CR), as manifested by a decreased HW/BW ratio and CSA and less collagen deposition after MH. XJEK administration also improved MH, as evidenced by decreased atrial natriuretic peptide (ANP), brain natriuretic peptide (BNP), and β -myosin heavy chain ( β -MHC) levels. XJEK also suppressed the decreased superoxide dismutase (SOD) and catalase (CAT) activities and increased malondialdehyde (MDA) levels in serum of mice with MH. XJEK-induced oxidative stress may be related to potentiating Nrf2 nuclear translocation and HO-1 expression compared with the MH groups. XJEK ameliorates MH by activating the Nrf2/HO-1 signaling pathway, suggesting that XJEK is a potential treatment for MH.